Reaksi Pasar atas Pengukuran Kinerja Akuntansi Perusahaan Prospector dan Defender : Analisis Dengan Pendekatan Life Cycle Theory - Tri Jatmiko Wahyu P.; Aprilia Diastini (Universitas Muhammadiyah Yogyakarta, Indonesia, 2007)
The study is an empirical study that intends to examine the difference accounting performance measures between prospector and defender strategies. The study also has objective to examine market reaction for both organizational strategies. Variables that implicated by organizational strategy are income growth, sales growth, dividend pay out, and return on investment. Life cycle theory approach is used to analyze the difference accounting performance measures. Four variables are used to explain strategies between prospector and defender firms are price to book value (PBV) ratio, sales to employee ratio, capital expenditure to market equity value ratio, and capital expenditure to total assets ratio. The sample are 30 to prospector firms, and 30 to defender firms derived from 60 manufacturing public firms at Jakarta Stock Exchange, tested by Principal Component Analysis. The result show that income and sales growth of prospector firms are greater than defender firms (significant at 0,01 level). Dividend pay out and return on investment of prospector firms are smaller than defender firms (significant at 0,01 level). While, the market reaction of prospector firms are greater than defender firms, the difference significantly at 0,01 level. Multivariate analysis is used to determine the difference level between prospector and defender firms and it relationship with stock price. The result show that there are significantly difference between income growth, sales growth, dividend pay out, and return on investment to abnormal return.